PENGARUH CURRENT RATIO (LDR) DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP RETURN ON ASSETS (ROA) PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI - Martha Rianty; Noviarni Noviarni (Universitas Tridinanti, 2022)
This study examines the Effect of Current Ratio (LDR) and Loan to Deposit Ratio (LDR) on Return On Assets (ROA) in Banking Companies Listed on the IDX. Basically, this thesis discusses how the Effect of Current Ratio (LDR) and Loan to Deposit Ratio (LDR) on Return On Assets (ROA) to measure the company's ability to pay off the company's debt can be measured from the level of liquidity of the company itself. While debt is one of the factors of a company's profitability. This study uses analytical methods, namely quantitative methods, descriptive statistical tests, classical assumption tests, multiple regression analysis, coefficient of determination tests, and hypothesis testing. The population in this study is 45 banking companies listed on the IDX from 2018-2020 with the observation period of the annual report published by Bursa Efek Indonesia, which is 12 observation samples.Keywords: Current Ratio, Loan to Deposit Ratio and Return On Asset